(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: This experiment was designed to investigate the morphological characterization of the brain cortices of African giant rats, AGR (Cricetomys gambianus, Waterhouse) across age groups as related to function. A total of 15 male AGR were used for this study comprising of 5 neonates, 5 juveniles and 5 adults. Brains were described as having typical rodent features; the falx cerebri, the dura modification of interest, was partly inserted between the lobes of the olfactory bulb and extended towards the corpus callosum. Gross parameters extrapolated include cerebral and cerebellar cortical dimensions using a one-way ANOVA (p≤0.05). Most values showed highest significant value bias for juveniles over adults and neonates. The average brain weight was 5.60±0.06g, 4.64±0.17g and 0.62±0.08g; cortex volume: 2.84±0.04cm3, 3.16±0.10cm3 and 0.23±0.02cm3 and antero-posterior dimensions: 11.93±0.26mm, 14.54±0.22mm and 6.00±0.16mm for adult, juvenile and neonates respectively. There was however adult bias in the cerebellum weight (0.83±0.02g, 0.76±0.02g and 0.04±0.02g); vermis length (13.23±0.32mm, 11.27±0.014mm and 0.24±0.02mm) and the antero-posterior length values (8.79±0.19mm, 6.97±0.03mm and 0.29±0.01mm) for adults, juveniles and neonates AGR respectively. Cortical parameters were related as a function of the brain development and plasticity, while age was described to play functional roles in intelligence determination of the AGR. The result of this study will be useful as baseline information for post mortem studies, medical imaging and useful as diagnostic tool for future research work on the AGR brain